2021
DOI: 10.3390/tropicalmed7010003
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety and Associated Factors among Frontline Hospital Healthcare Workers in the Fourth Wave of COVID-19: Empirical Findings from Vietnam

Abstract: (1) Background: This study aims to assess the magnitude of, and factors associated with, depression and anxiety among Vietnamese frontline hospital healthcare workers in the fourth wave of COVID-19; (2) Methods: A hospital based cross-sectional study was carried out within two weeks, October 2020, at a central COVID-19 treatment hospital. Depression and anxiety were measured with PHQ-9 and GAD-7, respectively. Bivariate and multivariate logistic regression analysis were applied to recognize variables related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 30 publications
0
23
1
1
Order By: Relevance
“…A previous study reported that only 33.1% and 5.5% of clinical health care workers in Vietnam experienced mild-to-severe and moderate-to-severe symptoms of anxiety, respectively (Quang et al, 2021). Another recent study noted that 25.5% and 4.3% of healthcare workers in Vietnam exhibited mild-to-severe and moderate-to-severe anxiety symptoms, respectively (Doan et al, 2021). Few studies have investigated anxiety symptoms in Japanese immigrants during COVID-19; however, a recent study reported that 66.6% of Chinese residents in Japan exhibited mild-to-severe symptoms of depression immediately after the first wave of COVID-19 (Hu and Umeda, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study reported that only 33.1% and 5.5% of clinical health care workers in Vietnam experienced mild-to-severe and moderate-to-severe symptoms of anxiety, respectively (Quang et al, 2021). Another recent study noted that 25.5% and 4.3% of healthcare workers in Vietnam exhibited mild-to-severe and moderate-to-severe anxiety symptoms, respectively (Doan et al, 2021). Few studies have investigated anxiety symptoms in Japanese immigrants during COVID-19; however, a recent study reported that 66.6% of Chinese residents in Japan exhibited mild-to-severe symptoms of depression immediately after the first wave of COVID-19 (Hu and Umeda, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…[18] Another recent study noted that 25.5% and 4.3% of healthcare workers in Vietnam exhibited mild-to-severe and moderate-to-severe anxiety symptoms, respectively. [14] Ueda et al [29] reported mild-to-severe symptoms of anxiety in 31.6% of Japanese people 18 years and older, based on GAD-7 scores. As observed for depressive symptoms, the prevalence of anxiety appears to be similar between Vietnamese immigrants and other immigrant populations in Japan, with immigrants experiencing more severe symptoms than Japanese and Vietnamese individuals living in their home countries.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations